Assessing and Modeling Discomfort Glare for Raw White LEDs with Different Patterns. Issue 2 (3rd April 2017) - Ma, Shining; Yang, Yang; Luo, Ming Ronnier; Liu, Xiaoyu
ABSTRACT: This article describes an experiment carried out to evaluate discomfort glare of nonuniformly distributed light emitting diode (LED) sources. The glare sources were created with a 4 × 4 LED panel. Twenty participants evaluated 140 lighting conditions consisting of eight nonuniformity patterns, four to five levels of luminous intensity, two levels of background luminance, and two angles above the line of sight. Some clear trends were found: discomfort glare was greater when the light source was less uniform and with higher LED luminous intensity, darker background, or a smaller angle above the line of sight. The unified glare rating (UGR) model for small glare sources (UGRsmall ) was tested using the experimental data. Although the UGR model had good correlation with visual results, it underestimated perceived glare. In addition, the degree of uniformity of the glare source was found to influence the performance of UGRsmall . As nonuniformity increases, the performance of UGRsmall decreases. Three modified versions of UGRsmall were derived, where each of the proposed models better predicts discomfort glare from nonuniform raw LED glare sources.